2021
DOI: 10.15408/insaniyat.v6i1.21141
|View full text |Cite
|
Sign up to set email alerts
|

Multilingualism in Sunan Ampel Tomb Complex: A Linguistic Landscape Study

Abstract: The present study focuses on the languages operating on the written signage that contribute directly to theformation of the linguistic landscape. The study chose Sunan Ampel Tomb in Surabaya, Indonesia, as one ofthe sites that has become a heritage conservation due to the history hidden in the site. This site is a part of the other sites in a series leading to the history of nine saints (Wali Songo) who brought Islam to Indonesia through one of the islands, Java. The study aimed at describing the linguistic la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Korean and German languages were only observed in one signage in the Faculty of Cultural Studies. The use of multilingual patterns in signage has also been identified in previous studies, which found that multilingual signs in a particular area tend to be limited in number [10,8]. Even in a limited number, multilingual signage includes languages that are studied in the Faculty of Cultural Studies.…”
Section: Languages In the Faculty Of Cultural Studiesmentioning
confidence: 61%
See 1 more Smart Citation
“…Korean and German languages were only observed in one signage in the Faculty of Cultural Studies. The use of multilingual patterns in signage has also been identified in previous studies, which found that multilingual signs in a particular area tend to be limited in number [10,8]. Even in a limited number, multilingual signage includes languages that are studied in the Faculty of Cultural Studies.…”
Section: Languages In the Faculty Of Cultural Studiesmentioning
confidence: 61%
“…However, the presence of linguistic landscape in the context of the Indonesian educational field has been contradictory. The presence of signage in the educational field arguably can help students with language or cultural awareness, but not all the texts are relevant to language learning [7], [1], [3], [8], and [5]. Several articles stated that the multimodality of a linguistic landscape helps communicative skills such as pragmatics, vocabulary, and grammar.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 displays commercial signs dominating the data, and only 13 % of the analyzed signs was public signs. The domination of bottom-up LL studies in Indonesia seems to relate to the language policy in Indonesia requiring Indonesian to be used on building names and other inscriptions in public area which is more probably applied by the government institutions (Andriyanti, 2019;da Silva et al, 2021;Fakhiroh & Rohmah, 2018;Harbon & Halimi, 2019a;Nuswantara et al, 2021;Riani et al, 2021;Wafa & Wijayanti, 2018) The huge number of the bottom-up signs were used as data sources in LL research on various places. First, restaurant names in Gresik Kota Baru (GKB), Purwokerto, and Pontianak; food/nutrition signs/texts in school-spaces in Jakarta and Depok; Batak Toba restaurants in Jakarta; as well as names of halal food stalls and restaurants in Malang and Taliwang.…”
Section: Figure 4 Top-up and Bottom-up Signs In Indonesian Ll Studiesmentioning
confidence: 99%
“…Figure4displays commercial signs dominating the data, and only 13 % of the analyzed signs was public signs. The domination of bottom-up LL studies in Indonesia seems to relate to the language policy in Indonesia requiring Indonesian to be used on building names and other inscriptions in public area which is more probably applied by the government institutions(Andriyanti, 2019;da Silva et al, 2021;Fakhiroh & Rohmah, 2018; Harbon & Halimi, 2019a;Nuswantara et al, 2021;Riani et al, 2021;Wafa & Wijayanti, 2018). This policy is mentioned in the National Constitution 1945, Decree of the People's Consultative Assembly Number 11/MPR/1983, Language Law number 24 Year 2009 and the most current regulation, President Regulation No.…”
mentioning
confidence: 99%
“…Meanwhile in Indonesia, research on multilingualism in the study of the linguistic landscape at the Sunan Ampel Cemetery Complex in Surabaya was conducted by Nuswantara, Firdausiyah, Rohmah, and Sholihah (2021). In addition, the linguistic landscape in the Indonesian context has also been conducted which focused more on the hotels and restaurants in Bali by Artawa, Paramarta, Mulyanah, and Atmawati (2023).…”
Section: Introductionmentioning
confidence: 99%